2022
DOI: 10.1038/s41598-021-04394-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state optical properties of self-assembling amyloid-like peptides with different charged states at the terminal ends

Abstract: The self-assembling of small peptides not only leads to the formation of intriguing nanoarchitectures, but also generates materials with unexpected functional properties. Oligopeptides can form amyloid-like cross-β assemblies that are able to emit intrinsic photoluminescence (PL), over the whole near-UV/visible range, whose origin is still largely debated. As proton transfer between the peptide chain termini within the assembly is one of the invoked interpretations of this phenomenon, we here evaluated the sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…However, very recent experiments by Accardo et. al on amyloid fibrils revealed a similar fluorescence intensity for protonated or zwitterionic ends, challenging some of these interpretations …”
Section: Molecular Origins Of Non-aromatic Fluorescencementioning
confidence: 61%
See 1 more Smart Citation
“…However, very recent experiments by Accardo et. al on amyloid fibrils revealed a similar fluorescence intensity for protonated or zwitterionic ends, challenging some of these interpretations …”
Section: Molecular Origins Of Non-aromatic Fluorescencementioning
confidence: 61%
“…al on amyloid fibrils revealed a similar fluorescence intensity for protonated or zwitterionic ends, challenging some of these interpretations. 42 Grisanti et al have recently provided an alternative molecular interpretation of the near-UV−vis non-aromatic emission energies. When molecular geometries of amides in amyloid proteins deviate from planarity, the amides CO and CN bonds elongate (Figure 3), and the ground state is slightly destabilized while the nπ* excited states are considerably stabilized (>1.0 eV).…”
Section: ■ Non-aromatic Fluorescencementioning
confidence: 99%
“…Using the high electric fields associated with the electrospinning methodology, Boc‐FF, dissolved in DCM or ethanol, was incorporated in three different polymers, specifically poly(L‐lactic acid) (PLLA, MW=225 KDa), polymethylmethacrylate (PMMA, MW=120 KDa) and poly‐3‐caprolactone (PCL, MW=80 KDa). As other phenylalanine containing peptides, [19] all the electrospunned systems showed an intense blue emission, ascribable to radiative decay of excitons. In addition, due to the high number of analogues containing aromatic groups, this group was further subclassed considering the number of aromatic rings composing the end‐capping moiety and the eventual presence of heteroatoms like nitrogen or oxygen into the structure.…”
Section: Description Of Fmoc‐ff Analoguesmentioning
confidence: 71%
“…They also suggested that proton delocalization between the charged ends of the chains could play a significant role. This suggestion, however, was not corroborated by a systematic analysis of the fluorescence emission of hexa-phenylalanine variants endowed with different charged states, which all presented similar spectroscopic properties [85]. More recently, it has been proposed that the deplanarization of the amide groups makes possible the excitation in the near-UV.…”
Section: Open Issues: the Electronic Basis Of The Fluorescence Emissi...mentioning
confidence: 96%